Kajian Pengaruh Suhu Pemanasan Awal Dan Waktu Sokletasi Terhadap Perolehan Minyak Biji Kelor (Moringa Oleifera Lam.) - Handayani, Sri Seno; Gunawan, Erin Ryantin; Suhendra, Dedy; Murniati, Murniati (LPPM Universitas Mataram, 2024)
Sound healing, or commonly referred to as music therapy using Acoustic Sound for Wellbeing (ASW) Moringa seed oil (Moringa oleifera Lam.) has significant potential for use in various industrial sectors, including food, pharmaceuticals, and cosmetics. One of the critical factors influencing oil extraction efficiency is preheating treatment and extraction process duration. This study aims to evaluate the effect of varying preheating temperatures and Soxhlet extraction times on the yield of Moringa seed oil, as well as to determine the most optimal extraction conditions. The extraction process was conducted using the Soxhlet method with n-hexane as the solvent. Preheating temperatures used in this study ranged from room temperature to 50°C, 60°C, and 70°C, with extraction times of 2, 4, and 6 hours. The results showed that preheating treatment on moringa seeds and extraction duration had a significant impact on oil yield. The optimal conditions were achieved at a preheating temperature of 70°C with an extraction time of 6 hours, yielding the highest oil recovery of 41.74%.